Penalaran Moral Mahasiswa dalam Layanan Bimbingan dan Konseling - Ria Hayati; Nengsih Nengsih; Dyla Fajhriani N (Prodi Bimbingan dan Konseling Islam, 2023)
Good moral education can potentially create human beings who are faithful, devoted and have intellectual intelligence. Ideally students as agents of change must be able to bring change in society, nation and state. Students should have moral reasoning according to their developmental tasks, namely in the conventional post stage. But in reality students' moral reasoning is still in the conventional stage. The purpose of this study is to know the description of student moral reasoning. This research is using experimental method. The study population was students of the Faculty of Education, Padang State University. The research sample was students of Guidance and Counseling. The sampling technique uses cluster sampling. Data analysis using the Wilcoxon Signed Ranks Test. The results of the study found that students' moral reasoning is still classified as a conventional stage with a low category, it is expected that the presence of the latest methods or approaches can be a reference in guidance and counseling.